Exploring Perception of Indians about Plain Packaging of Tobacco Products: A Mixed Method Research - Arora, Monika; Tewari, Abha; Nazar, Gaurang P.; Grills, Nathan; Sonrexa, Juhi; Gupta, Vinay K.; Moodie, Rob; Reddy, K S. (Frontiers in Public Health, 2013)
This study assessed perceptions and support among the Indian populace about plain packaging for all tobacco products.12 focus group discussions (n=124), stakeholder analysis with 24 officials and an opinion poll with 346 participants were conducted between December 2011 - May 2012 , Delhi. Plain packages for tobacco products were favoured by majority of participants (69%) and key stakeholders (92%). The majority of participants perceived that plain packaging would reduce the appeal and promotional value of the tobacco pack (>80%), prevent initiation of tobacco use among children and youth (>60%), motivate tobacco users to quit (>80%), increase noticeability and effectiveness of pictorial health warnings on tobacco packs (>90%),reduce tobacco usage (75% of key stakeholders). Majority of participants favoured light grey colour for plain packaging. This study provides key evidence to advocate with Indian Government and other countries in South Asia region to introduce plain packaging legislation for all tobacco products.